Síntese de compósitos magnéticos ferrita/quitosana para adsorção de corantes e fármacos - Santos, Juliana Machado Nascimento dos (2019)
Water is a cornerstone to the flourishment of any existing life form and as such, need to be preserved. Working on development and improvement of technologies which promote an efficient effluent treatment, preventing pollutant molecules to reach water bodies, is to work in favor of this preservation. In this study, adsorbent composites with magnetic properties, CoFe2O4/chitosan and ZnFe2O4/chitosan, were produced without any calcination step and applied for indigotine blue dye (IBD) and potassium diclofenac (DCF) adsorption. The FT-IR, XRD, BET, SEM, EDS and VSM analysis, carried out for composite characterization purposes, suggested that adsorbent particles were formed by a chitosan external layer and ferrite as core material. VSM results proved that a simple magnetic field is sufficient to promote solid/liquid separation after the adsorption process. CoFe2O4/chitosan magnetic composite was an excellent adsorbent for IBD removal from aqueous solution. Using initial pH of 3.0 and 0.75 g L–1 as adsorbent dosage, adsorption equilibrium was attained at 15 min of operation. The maximum adsorption capacity, estimated by the Langmuir model, was 380.8 mg g–1, at 328 K. From thermodynamic viewpoint, IBD adsorption onto CoFe2O4/chitosan was a spontaneous, endothermic and favorable process. The DCF adsorption using ZnFe2O4/chitosan was also a rapid process, favored at initial pH 4 and when 0.2 g L-1 was used as adsorbent dosage, reaching equilibrium in 20 min. The S-shaped equilibrium isotherms, which indicate a cooperative adsorption, were systematically predicted by BET multilayer liquid-phase model. DCF adsorption was a spontaneous, exothermic and favorable process, mainly at 298 K, where higher values of adsorption capacity (188 mg g-1) were observed. The ZnFe2O4/chitosan adsorbent composite exhibited reuse potential, maintaining the original capacity, during four adsorption cycles. The synthesis method proposed by this work is simple, does not require fancy equipment, nor demand high temperature or controlled atmosphere operating conditions to avoid materials oxidation. When combined with fast kinetics and high adsorption capacities verified, it makes the magnetic adsorbent composites formed a viable and efficient alternative for dyes and drugs adsorption.